Advanced Piezoelectric Materials, Devices, and Systems for Orthopedic Medicine - Jingkai Zhang; Chang Liu; Jun Li; Tao Yu; Jing Ruan; Fan Yang (Advanced Science, 2025)
Abstract Harnessing the robust electromechanical couplings, piezoelectric materials not only enable efficient bio‐energy harvesting, physiological sensing and actuating but also open enormous opportunities for therapeutic treatments through surface polarization directly interacting with electroactive cells, tissues, and organs. Known for its highly oriented and hierarchical structure, collagen in natural bones produces local electrical signals to stimulate osteoblasts and promote bone formation, inspiring the application of piezoelectric materials in orthopedic medicine. Recent studies showed that piezoelectricity can impact microenvironments by regulating molecular sensors including ion channels, cytoskeletal elements, cell adhesion proteins, and other signaling pathways. This review thus focuses on discussing the pioneering applications of piezoelectricity in the diagnosis and treatment of orthopedic diseases, aiming to offer valuable insights for advancing next‐generation medical technologies. Beginning with an introduction to the principles of piezoelectricity and various piezoelectric materials, this review paper delves into the mechanisms through which piezoelectric materials accelerated osteogenesis. A comprehensive overview of piezoelectric materials, devices, and systems enhancing bone tissue repair, alleviating inflammation at infection sites, and monitoring bone health is then provided, respectively. Finally, the major challenges faced by applications of piezoelectricity in orthopedic conditions are thoroughly discussed, along with a critical outlook on future development trends.